The effect of post-activation potentiation in the sprint in freestyle (International Seven Journal of Multidisciplinary, 2023)
Post-Activation Potentialization (PPA) is defined as an acute improvement in muscle function after stimulation. Different variables of PPA protocols can affect performance, such as the duration, the type of stimulus, the level of training of the requirements and the time interval between the conditioning activity and the specific activity. In the Swimming sport, there is a recurring debate between the types of warm-ups that could benefit practitioners the most. From this, the interest in understanding the relationship between pre-sprint activity and performance in it arose. The objective of the present study was to identify the effect of PPA performed in aquatic or terrestrial environments, on the performance of the sprint performed in freestyle. The sample consisted of 19 individuals of both sexes, who have been swimming for at least one year. Professionals in the area of ​​Physical Education consented to the tests that were applied in the research, they took place based on three protocols entitled "Control", "aquatic PPA" and "terrestrial PPA", on different days, with an interval between them and the entry was alternating. The researchers analyzed the data and, when comparing the three protocols, it was observed that 68% of the sample had the best sprint time in the control protocol, without the post-activation potentiations. Only six participants improved the time compared to the control, but it is an indication that the PPA is capable of enhancing performance depending on the methodology applied. When analyzing only the two PPA protocols, it was found that 12 of the 19 participants had the best sprint time after aquatic PPA, and only seven people after the terrestrial PPA protocol. Thus, it was possible to understand that the aquatic PPA had more satisfactory results in relation to the other potentiation protocol and this conclusion occurred regardless of gender.DOI: 10.56238/isevmjv1n2-001